A Call for Improved Screening of Preoperative Prescription Drug Abuse: A Scalar Assessment Not Limited to Opioids. Issue 2 (22nd June 2021) - Emara, Ahmed K.; Klika, Alison K.; Piuzzi, Nicolas S.
Abstract : Prescription-drug abuse has strained US healthcare. While several investigations highlight an association between opioid use and adverse postoperative outcomes, similar associations with nonopioid prescription-drugs remain under-studied. Furthermore, patients' underlying prescription drug use patterns remain poorly characterized. This perspective details such obstacles which hinder translating literature-reported findings into practice.